Vitamin B12 - is it worth supplementing? - Wojaczek, Marta; Polańska, Katarzyna; Kahan, Weronika; Szafrańska, Weronika; Poborowska, Dominika; Bąk, Emilia; Fordymacki, Jacek; Najjar, Oliwia; Gańko, Tomasz (Quality in Sport, 2024)
Abstract Introduction Cobalamin is a vitamin that plays an important role in many processes occurring in our body. It affects, among others, the functioning of the hematopoietic, nervous, and digestive systems and the functioning of the psyche. Its deficiency can be encountered in everyday clinical practice. Many scientific studies have been conducted on it, focusing on the causes and effects of its deficiency. Purpose This work aims to identify groups of patients whose risk of vitamin B12 deficiency is higher than in the general population. This will help draw attention to these selected groups of patients, so that in clinical practice, vitamin B12 supplementation may be considered before symptoms of its deficiency occur. Brief description of the state of knowledge The most common cause of vitamin B12 deficiency is Addison-Biermer's disease caused by the presence of autoantibodies against Castle's intrinsic factor. However, there are more factors that indirectly affect the level of cobalamin in the body. Material and methods In this work, we analyzed the following conditions and diseases that are correlated with vitamin B12 deficiency: medications taken, gastrointestinal diseases, conditions after bariatric surgery, pregnancy, vegan diet, old age, and alcohol. Discussion: After analyzing selected issues, we conclude that the risk of vitamin B12 deficiency varies, in some cases, it is correlated with advanced disease, and in others, it is independent of it. Additionally, it should be taken into account that although the pathomechanism leading to vitamin B12 deficiency is known in the above-mentioned conditions, the real risk of its deficiency may be so low that its clinical significance will be low.